Educational Leadership in Ecuadorian Technical Schools: A Qualitative Analysis of Policy Impact on Leadership Practices (Investigaciones) - Moreno Vásconez, Oscar Alexander (2025)
Educational leadership has garnered significant attention in Western research over the past two decades. However, in Latin America, it has only recently become a focus of study. Much of the existing research applies leadership concepts without adequately considering the unique political, cultural, and social contexts of individual countries. Ecuador, in particular, has undergone numerous educational reforms in the past fifteen years, significantly altering its educational landscape and leadership practices. This study investigates the leadership practices of educational leaders in Ecuadorian technical schools, specifically focusing on setting directions, developing people, and re-culturing schools. Through interviews and document analysis, the study reveals that educational leaders aim to redesign school organisations collaboratively by integrating efforts from students, parents, and teachers to achieve collective goals. They also navigate administrative duties while fostering a supportive environment for teachers and students. The study identifies factors influencing these practices, such as educational reforms and leadership responsibilities, and addresses challenges like strained professional relations and resistance from experienced teachers. These findings underscore the importance of a collaborative and distributive leadership approach tailored to Ecuador’s unique social and educational context. This research contributes to advancing contextualised educational leadership knowledge in Ecuador.